Flouting Maxims in INSIDE OUT 2 Movie - Dewi Putri Basani Simarmata; Tesalonika L.A; Shandy Prasetyo; Dylan Adji Pratama (Linguistik : Jurnal Bahasa dan Sastra, 2026)
Movies often serve as more than just sources of entertainment, as they also reflect the complexities of real-life human communication. Dialogues in movies capture how people interact, including instances where speakers intentionally deviate from expected conversational norms. This study investigates the flouting of Grice’s conversational maxims in Inside Out 2, an animated movie that explores the emotional and psychological development of a teenage girl named Riley. Previous studies have discussed maxim flouting in various movies, yet little attention has been given to how such pragmatic strategies appear in characters experiencing emotional growth and adolescence. This research aims to fill that gap by identifying the types and functions of flouted maxims in Inside Out 2. Using a descriptive qualitative and documentation method, the researcher collected data by watching the movie repeatedly and cross-checking the dialogues with its official transcript. The findings reveal 21 instances of maxim flouting: quantity and quality were each flouted eight times (38%), relation four times (19%), and manner once (5%). The results were compared with findings from the first Inside Out, revealing differences in the types and contexts of flouting influenced by the introduction of new characters and Riley’s changing emotional and psychological states during adolescence.